The impact of low- versus standard-volume bowel preparation on participation in primary screening colonoscopy: a randomized health services study - Pisera, Małgorzata; Franczyk, Robert; Wieszczy, Paulina; Polkowski, Marcin; Rupinski, Maciej; Chaber-Ciopinska, Anna; Kotowski, Bronislaw; Kula, Zbigniew; Kielek, Slawomir; Buszkiewicz, Marek; Rupinska, Maria; Kobiela, Jaroslaw; Kaminski, Michal Filip; Regula, Jaroslaw (Endoscopy, 2019)
Background The aim of this study was to evaluate the impact of low-volume vs. standard-volume bowel preparation on participation in screening colonoscopy, bowel preparation quality, and lesion detection rates.Methods This was a multicenter, randomized, health services study within the population-based primary colonoscopy screening program in Poland. Individuals aged 55 – 62 years were randomized in a 1:1 ratio to bowel preparation with a low-volume (0.3 L sodium picosulfate with magnesium citrate) or standard-volume (4 L polyethylene glycol) regimen and then invited to participate in screening colonoscopy. The primary outcome measure was the rate of participation in screening colonoscopy. Compliance with the assigned bowel preparation, bowel preparation quality, and lesion detection rates were also evaluated.Results A total of 13 621 individuals were randomized and 13 497 were analyzed (6752 in the low-volume group and 6745 in the standard-volume group). The participation rate (16.6 % vs. 15.5 %; P = 0.08) and compliance rate (93.3 % vs. 94.1 %; P = 0.39) did not differ significantly between the groups. In the low-volume group, fewer participants had adequate bowel preparation compared with the standard-volume group (whole colon 79.0 % vs. 86.4 %, P < 0.001; proximal colon 80.1 % vs. 87.3 %, P < 0.001). Detection rates of advanced adenoma (AADR) and advanced serrated polyps (ASPDR) were lower in the low-volume group than in the standard-volume group (AADR in the proximal colon 2.6 % vs. 4.3 %, P = 0.02; ASPDR in the whole colon 2.0 % vs. 3.3 %, P = 0.04; ASPDR in the proximal colon 1.0 % vs. 1.9 %, P = 0.048). Conclusion When compared with a standard-volume bowel preparation with polyethylene glycol, low-volume bowel preparation with sodium picosulfate/magnesium citrate did not improve participation rate or lesion detection rates, and negatively affected bowel preparation quality.